Residual ridge resorption, the effect on prosthodontics management of edentulous patient: an article review: residual ridge resorption (International Journal of Scientific Research and Management (IJSRM), 2019)
Bone resorption is a chronic, progressive disease and irreversible process that occurs in all patients and can be classified into six different types. There are some of etiological factors that may cause resorbed ridge such as anatomical, prosthodontics, metabolic and systemic factors. The present article, were reviewed the literature concerning on possible mechanism, diagnosis, etiological factors and how to manage and prevent of resorbed ridge for edentulous patients